EXPLORATION OF INNOVATION ATTRIBUTES ON INTENTION AND ADOPTION OF VIRTUAL REALITY (VR) IN ENTERTAINMENT - Alankriti Tiwari , Madhavi Damle (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Virtual Reality (VR) is an immersive technology that enables a user to experience a real world in a virtually created environment. With this progressive technology, the experience of a user is enhanced in terms of entertainment. The paper explores the perception-based study of VR Technology, especially in Entertainment, based on innovation attributes from Roger’s Diffusion Model of Innovation Theory along with cost as an additional attribute that will influence the behavioural intention and adoption of the consumer. The five attributes utilized were complexity, compatibility, relative advantage, observability, and trialability along with cost from which the hypotheses were made. The analysis was done using the reliability tests, and regression by computing the constructs based on the responses. The attributes were studied against behavioural intention whereas cost and behavioural intention were studied against adoption. Except complexity, all other attributes showcased significant relationships with behavioural intention. Also, behavioural intention and cost showcased a significant relationship with the adoption. Although, further studies can be done using more innovation attributes by incorporating individual aspects (features, benefits, applications, and concerns) in the context of VR in entertainment.